Radar Studies of Subglacial Lake Whillans and the Whillans Ice Stream Grounding Zone - Jacobel, Robert (IEDA: US Antarctic Program Data Center, 2014)
Abstract: This data set includes ground-based, gridded, ice-penetrating radar thickness and basal reflection power, along with GPS coordinates, for two areas of Whillans Ice Stream: Subglacial Lake Whillans and the Whillans Ice Stream grounding zone.